2017
DOI: 10.1007/s40263-017-0434-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Aβ42 Anti-Aggregation Mechanism of Action of Tramiprosate in Alzheimer’s Disease: Integrating Molecular Analytical Methods, Pharmacokinetic and Clinical Data

Abstract: BackgroundAmyloid beta (Aβ) oligomers play a critical role in the pathogenesis of Alzheimer’s disease (AD) and represent a promising target for drug development. Tramiprosate is a small-molecule Aβ anti-aggregation agent that was evaluated in phase III clinical trials for AD but did not meet the primary efficacy endpoints; however, a pre-specified subgroup analysis revealed robust, sustained, and clinically meaningful cognitive and functional effects in patients with AD homozygous for the ε4 allele of apolipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 46 publications
(66 reference statements)
3
102
1
Order By: Relevance
“…Nevertheless,ithas been shown that multi-ligand interactions of tramisprosate with monomeric Ab42 can prevent amyloid oligomer formation. [25] Hydrophobic small molecules can form colloids that resemble protein liquid droplets in size. [7] These small-molecule colloids are,h owever, unspecific inhibitors,a st hey interact promiscuously with hydrophobic regions of aprotein and eventually induce protein unfolding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless,ithas been shown that multi-ligand interactions of tramisprosate with monomeric Ab42 can prevent amyloid oligomer formation. [25] Hydrophobic small molecules can form colloids that resemble protein liquid droplets in size. [7] These small-molecule colloids are,h owever, unspecific inhibitors,a st hey interact promiscuously with hydrophobic regions of aprotein and eventually induce protein unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Thedesign of the ISMs was based on the finding that amyloids are generally composed of a b-sheet-turn-b-sheet structural motif and that IAPP uses the same two binding regions for both its amyloid self-and its cross-amyloid hetero-assembly with Ab40/42. [1a, 2] ISMs were thus derived by linking the two hot segments IAPP (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and IAPP (22)(23)(24)(25)(26)(27)(28) in native or N-methylated form to each other via different linkers,mostly tripeptide sequences consisting of identical amino acids;notably,these two segments are highly homologous to segments of the amyloid core of Ab. [3] High Ab40/42 anti-amyloidogenic activity was found for seven out of the 16 studied ISMs with six of them containing bulky hydrophobic/aromatic residues (e.g.L LL, III, FFF) in the linker tripeptide and one of them, termed R3-GI, the RRR tripeptide.…”
Section: Introductionmentioning
confidence: 99%
“…This substance may interfere with several cellular pathways and exert neuroprotective and neurotropic activities through different mechanisms including effects against the oxidative damage to DNA, antifibrillogenic activity, and antinociceptive and analgesic activities, related to the activation of GABA type-A receptors. In addition, homotaurine prevents the neurotoxicity of Aβ peptide by reducing amyloid aggregation in humans [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Tramiprosate is an oral amyloid anti-aggregation agent that reduces oligomer formation and fibrillar (plaque) amyloid deposition in transgenic animal models (14). Tramiprosate has been shown to inhibit β-amyloid (Aβ) fibrillation and to reduce soluble Aβ.…”
mentioning
confidence: 99%
“…It has also been reported to inhibit the inflammatory response. More recently, tramiprosate has been shown to modulate “conformational flexibility of amyloid beta Aβ42, leading to the prevention of oligomer seed formation and thus aggregation” (4). …”
mentioning
confidence: 99%